Observations of the neutral hydrogen surrounding the radio-quiet neutron star RX J0822-4300 in Puppis A - Reynoso, Estela Marta (2003)
We have observed the H i distribution in an area 40 × 40 arcmin2 around the neutron star candidate RX J0822–4300, which is located in the supernova remnant Puppis A. The observations of the λ21-cm line were obtained with the Australia Telescope Compact Array and were combined with single-dish data from the Southern Galactic Plane Survey. The spatial resolution is 90 arcsec, and the velocity resolution is 1 km s−1. A sensitivity of ∼0.7 K was achieved. The results revealed a double-lobed feature of reduced emission at +16 km s−1, centred on the central compact object (CCO), and aligned with an H i hole blueshifted by 13 km s−1. The H i depressions have probably been created by the sweeping up of ∼2 M⊙. The alignment between the lobes and the optical expansion centre of Puppis A suggests that the CCO could be ejecting two opposite jets. The velocity at which the two lobes are best defined has allowed us to confirm that the distance to Puppis A is 2.2 kpc, based on a systemic velocity of +16 km s−1 . The hydrogen column density computed using this systemic velocity is consistent with estimates from models for X-ray spectra, thus reinforcing our conclusion that the kinematic distance is 2.2 kpc.